2009
DOI: 10.3748/wjg.15.4016
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of gastric H,K-ATPase by cigarette smoke extract

Abstract: AIM:To test whether the expression and activity of H,K-ATPase in parietal cells would be affected by cigarette smoke extract.METHODS: E x t ra c t s o f c i g a r e tt e s m o ke w e r e administered into mice by gastric gavage (5 mg/kg body weight/day) for 3 d or in drinking water for 7 or 14 d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A somewhat speculative connection is offered by recent work, which showed cigarette smoke extracts cause an increase in the amount of H + /K + ATPase in the stomach [28]. It is unclear — and worth testing — whether ATP4A and ATP4B are expressed in the heart.…”
Section: Resultsmentioning
confidence: 99%
“…A somewhat speculative connection is offered by recent work, which showed cigarette smoke extracts cause an increase in the amount of H + /K + ATPase in the stomach [28]. It is unclear — and worth testing — whether ATP4A and ATP4B are expressed in the heart.…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced secretion of acid and pepsin by parietal and zymogenic cells may contribute to damage of the mucous layer ( 1 ). Smoking contributes to ulcer formation by upregulating the production of the proton pump and, therefore, acid secretion ( 19 ). Damage to the mucous layer may lead to peeling of the surface epithelium and exposure of the endothelial cells of capillaries in the underlying connective tissue.…”
Section: Gastric Ulcermentioning
confidence: 99%
“…(Firmicutes) in the colon, with alteration in inflammatory gene expression. 231 These data highlight a possible role for CS in gut microbiome shaping with unknown consequences in the evolution of inflammation-related disorders such as IBD.…”
Section: Ibd Microbiome and Lifestyle Factorsmentioning
confidence: 89%
“…Among them, the following should be mentioned: epigenetic susceptibility, modulation of mucosal immune response, alterations in intestinal cytokine and eicosanoid levels, modification of gut permeability with consequent impaired clearance of pathogen alteration in the H þ /K þ -ATPase pump with consequential acidification of gastric contents, and ingestion of the bacteria present in cigarettes. [227][228][229][230]231,232 Human studies targeting selected bacterial groups have reported that smoking patients with active CD have increased abundances of Bacteroides and Prevotella 233 (both Bacteroidetes) and decreased Firmicutes to Bacteroidetes ratios. 60 Similar results were obtained in healthy CS controls, suggesting that the association may not be related to intestinal inflammation but may instead reflect the direct impact of CS on the microbiota.…”
Section: Ibd Microbiome and Lifestyle Factorsmentioning
confidence: 99%